Recuentos cromosomicos en especies de Hypochaeris L. (ASTERACEAE) de Chile (Gayana Botánica, 2000)
Karyotypes of two Chilean taxa of genus Hypochaeris were studied utilizing root-tip-mitotic metaphases. All the populations have karyotypes with 2n = 8 that are very uniform within each species. H. apargioides has a chromosome set 4m + 4st and H. radicata 4m + 2m-sat + 2sm.